Post Covid-19 Vaccination: What is the Description of Knowledge, Attitudes, Availability of Facilities and Community Compliance? - Fitri Yanti; Komang Ayi Sukma; Amaliah Rohman; Risa Dwi Violita (CORE JOURNAL, 2022)
Covid-19 has become a major problem throughout the world to date, has an impact on health and spreads to other joints of life. The Covid-19 vaccination program is currently underway. However, some post-vaccination people are negligent on health protocols because they feel they are already immune to the virus. This study aims to find out how the knowledge, attitudes, availability of facilities, and post-vaccination community compliance are related to Covid-19. This type of research is descriptive quantitative to describe an event that is happening. The population of this study is office workers in the Southeast Sulawesi region, amounting to 73,037 people. The sample is 284 office workers who have been vaccinated. The sampling technique is Snowball Sampling. Primary data collection through online questionnaires distributed to office workers who have been vaccinated. The data analysis of this research used univariate analysis and presented in the form of tables and narratives. The results showed that the majority of respondents had good knowledge (66.2%), had a positive attitude (99.6%), provided facilities and facilities (98.2%), and adhered to health protocols (97.5%). The recommendation of this research are the health institution to educate the community about covid 19 health ptotocol